Mac OS X 10.6 Snow Leopard : video quickstart guide - Langer, Maria (Peachpit Press, 2010)
"Mac OS X 10.6 Snow Leopard: Video QuickStart Guide will have you up and running in no time with Snow Leopard, the fastest and most reliable version of the Mac OS X ever. Respected, best-selling author Maria Langer takes you through all of Mac OS X's groundbreaking capabilities and features. Organized by task, Maria clearly illustrates key techniques and core tools with step-by-step explanations. From Finder basics and File management to networking, security, system preferences and utilities, everything is covered"--Resource description page.